Analisa Quality Assurance (QA) Daily Pada Pesawat Linac Di Instalasi Onkologi Radiasi RSUP Persahabatan - Irianti Fitri Ningsih; Kadek Yuda Astina; Burlian Mughnie (Universitas Hamzanwadi, 2025)
Linear Accelerator (Linac) plays a critical role in external radiotherapy for cancer treatment, requiring stringent quality assurance (QA) measures to ensure accuracy and safety. This study focuses on analyzing the implementation of daily QA for the Elekta Prices Linac model Precise at the Radiation Oncology Unit of RSUP Persahabatan. Conducted from May to July 2024, the analysis evaluates four key parameters: Laser Localization, Optical Distance Indicator (ODI), Door Interlock, and Audiovisual Monitor. The results demonstrate that all parameters met the tolerance limits set by AAPM Task Group 142, ensuring the Linac operates safely and effectively. Consistent implementation of daily QA is shown to detect potential deviations early, safeguarding both patient and staff safety while maintaining treatment quality.